2007
DOI: 10.1002/bsl.774
|View full text |Cite
|
Sign up to set email alerts
|

Police practices and perceptions regarding juvenile interrogation and interrogative suggestibility

Abstract: Recent media coverage has highlighted cases in which young suspects were wrongly convicted because they provided interrogation-induced false confessions. Although youth may be more highly suggestible and easily influenced by authority than adults, police are trained to use the same psychologically coercive and deceptive tactics with youth as with adults. This investigation is the first standard documentation of the reported interrogation practices of law enforcement and police beliefs about the reliability of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
94
1
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(105 citation statements)
references
References 54 publications
9
94
1
1
Order By: Relevance
“…This could be partly explained by the relative homogeneity of the sample, composed mainly of adult male Caucasian offenders aged in their thirties. Different results might have been observed had we included juvenile offenders, who are more likely to confess than adults (Meyer & Reppucci, 2007;Phillips & Brown, 1998), although this finding has not been consistent Leo, 2006;Moston et al, 1992).…”
Section: Discussionmentioning
confidence: 74%
“…This could be partly explained by the relative homogeneity of the sample, composed mainly of adult male Caucasian offenders aged in their thirties. Different results might have been observed had we included juvenile offenders, who are more likely to confess than adults (Meyer & Reppucci, 2007;Phillips & Brown, 1998), although this finding has not been consistent Leo, 2006;Moston et al, 1992).…”
Section: Discussionmentioning
confidence: 74%
“…to truthfully confess or not confess to a crime committed, or to falsely confess or not confess to a crime not committed) because of comprehension and reasoning impairments (see, e.g., Goldstein, Kalbeitzer, Zelle, & Romaine, 2006) and heightened suggestibility-they are more vulnerable than nondisabled juveniles to even subtle psychological influence, persuasion, deception, and coercion (Clare & Gudjonsson, 1993;Henry & Gudjonsson, 1999;Milne, Clare, & Bull, 2002;Young, Powell, & Dudgeon, 2003; but see . In light of evidence that police often use the same coercive interrogation strategies with children and youth as they do with adults (Meyer & Reppucci, 2007), there is substantial cause for concern that innocent disabled juveniles are at risk for falsely confessing to crimes they did not commit.…”
Section: Confession Evidencementioning
confidence: 99%
“…This dimension can be described as tricking a suspect into a ‘voluntary’ confession. It should be noted that the cases we labelled as manipulation are different from the trickery and deceit used by American interrogators (Feld, ; Kassin et al , ; Meyer & Reppucci, ). We found that suspects were presented with hypothetical situations in an attempt to elicit a statement such as an interrogator presenting the suspect with the scenario that he did not mean to kill the victim with the screw driver but only meant to stop him with it.…”
Section: The Dutch Interrogation Practicementioning
confidence: 86%